PENGARUH PENAMBAHAN PURSED LIPS BREATHING EXERCISE PADA STATIC CYCLE INTENSITAS SEDANG TERHADAP PENINGKATAN KEBUGARAN PADA PENDERITA PPOK - -, Setyawan; Khotimah, Siti (Sport and Fitness Journal, 2017)
Background: Chronic Obstructive Pulmonary Disease (CPOD) is a chronic lung disease identified which can be identified by the occurrence of a progressive nonreversible or reversible air detention in respiratory. One of the causes of CPOD is smoke. According to a report in Rumah Sakit Paru-paru Respira Yogyakarta, CPOD is the most visited disease in this hospital among other lung diseases. This disease results in inability of doing any activity and affects the level of fitness. Objective: This study aims to investigate the effect of adding pursed lips breathing exercise on a static cycle with moderate intensity toward the fitness enhancement of COPD patients. Method: This research was done using the quasi experimental and administered with pre and posttest for two groups. The researcher involved six respondents who were COPD inpatients and outpatients. The respondents were divided into two different groups which consist of three patients for each group with different treatments. The first group was given moderate intensity static cycle treatment three times a week in three weeks treatment. The second group was given additional pursed lips breathing exercise four times a day consecutively in four days on moderate intensity static cycle. The measurement of the fitness level was done with six-minute walking and put into the VO2 Max formulation. Then the research result was analyzed by using paired sample T-test and Wilcoxon. Result: Hence, the research results in the first hypothesis tested with paired sample T-test was p=0.160 (p>0.05) meaning that there were no effect of moderate intensity static cycle toward the fitness enhancement among the COPD patients. In the second group tested with Wilcoxon, it was found that p=0.109 (p>0.05). This implies that there was no effect of adding pursed lips breathing exercise on moderate intensity static cycle toward the fitness enhancement among the COPD patients. Conclusion: In conclusion, the effect of adding pursed lips breathing exercise on moderate intensity static cycle toward the fitness enhancement among COPD patients is absent. Suggestion: The researcher suggests to future researcher to add the number of respondents, the duration of the research and to equalize the COPD grade.